Trade contacts between Prague Jews and Northern Italy and their engagement in the Italian commodity trade in the 16th and early 17th centuries. - Buňatová, Marie (Židovské muzeum v Praze, 2019)
This study looks at contacts between Prague’s Jews and merchants in Italy’s market centres (Bolzano, Verona, Venice) during the period prior to the Battle of White Mountain. It also looks at the business activities of some Italian immigrants who operated in Rudolfine Prague.
Obchodní kontakty pražských Židů se severní Itálií a jejich zapojení do obchodu s italským kramářským zbožím v 16. a raném 17. století.
Keywords: Bohemia; Prague; Italy; Early modern period; Economic history; Trade; Jews; Čechy; Praha; Itálie; raný novověk; hospodářské dějiny; obchod; Židé